(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Four liquid-liquid extraction-chromogenic systems containing Fe(III), 4-(2-thiazolylazo)resorcinol (TAR), tetrazolium salt (TZS), water and chloroform were studied. 2,3,5-Triphenyl-2H-tetrazolium chloride (TTC), 3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-2H-tetrazolium bromide (MTT), 3-(2-naphtyl)-2,5-diphenyl-2H-tetrazolium chloride (TV), and 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-phenyl-2H-tetrazolium chloride (INT) were the examined TZSs. Optimization experiments for iron extraction were performed and the following parameters were found for each system: pH(opt), CTAR(opt), CTZS(opt), shaking time (opt), and l(opt). Under the optimum conditions, the molar ratio of the reacting Fe(III), TAR and TZS is 1:2:2 and the general formula of the extracted species is (TZ+)2[FeII(TAR2–)2]. Some equilibrium constants (constants of association, constants of distribution, and constants of extraction) and analytical characteristics (molar absorptivities, Sandell’s sensitivities, Beer’s law limits, etc.) were calculated. Linear relationships involving the molecular mass of TZ+ were discussed.